The Time for Chronotherapy in Radiation Oncology - Bermúdez-Guzmán, Luis; Blanco-Saborío, Alejandro; Ramírez-Zamora, Juliana; Lovo, Eduardo (Frontiers in Oncology, 2021)
Five decades ago, Franz Halberg conceived the idea of a circadian-based therapy for cancer, given the differential tolerance to treatment derived from the intrinsic host rhythms. Nowadays, different experimental models have demonstrated that both the toxicity and efficacy of several anticancer drugs vary by more than 50% as a function of dosing time. Accordingly, it has been shown that chemotherapeutic regimens optimally timed with the circadian cycle have jointly improved patient outcomes both at the preclinical and clinical levels. Along with chemotherapy, radiation therapy is widely used for cancer treatment, but its effectiveness relies mainly on its ability to damage DNA. Notably, the DNA damage response including DNA repair, DNA damage checkpoints, and apoptosis is gated by the circadian clock. Thus, the therapeutic potential of circadian-based radiotherapy against cancer is mainly dependent upon the control that the molecular clock exerts on DNA repair enzymes across the cell cycle. Unfortunately, the time of treatment administration is not usually considered in clinical practice as it varies along the daytime working hours. Currently, only a few studies have evaluated whether the timing of radiotherapy affects the treatment outcome. Several of these studies show that it is possible to reduce the toxicity of the treatment if it is applied at a specific time range, although with some inconsistencies. In this Perspective, we review the main advances in the field of chronoradiotherapy, the possible causes of the inconsistencies observed in the studies so far, and provide some recommendations for future trials.